Price theory - Friedman, Milton (Chicago : Aldine Publishing Company, 1976)
The book deals with price theory. The larger part is devoted to the principle of final product; the rest, to the theory of distribution.
Includes bibliographical references and index.
osa 19/12/2018
Loans
Keywords: Price theory